Pengaruh Harmonisasi Otak Terhadap Kemampuan Aktivitas Fungsional Ekstremitas Atas Pada Pasien Pasca Stroke - ANNUR, Fachrurozi Rofika, Umi Budi Rahayu, SSt. Ft. SPd. M. Kes, Wahyuni, SSt.FT.M.Kes (2015)
Background: Stroke is a major medical problem as the cause of death which is happening in today's society and the third largest cause of death in the world. Stroke is a disease that is the main cause of disability in the world. One the disability is a functional disorder of the upper extremity. Functional disorders of the upper extremity strongly inhibit activity of the patient. One of the therapeutic action to help the recovery of the upper extremity functional activity is harmonize the brain at the time of nerve regeneration after stroke. Activation of brain nerve through harmonization will stimulate the formation of substances that are essential for the growth of nerve cells. Objective: To investigate the harmonization effect on brain activity functional skills upper extremity post stroke patients. Methods: This Research use a Single Case Research approach with the design of the A-B-A for a month, the research sample is 2 persons. The sampling technique used purposive sampling method that establishes a sample based on the characteristics and particular characteristics that suitable with the inclusion criteria. Results and conclusions: Analysis of data in this research is using descriptive statistics with the purpose getting a detailed results description from intervention result within the prescribed period by using a line graph as a picture of the implementation and experimental results. Based on the analysis chart found that exercise the brain harmonizing effect on the increase in the ability of the functional activity of the upper extremity post-stroke patients with the results of each of the subjects research is 61.9% and 37.9%.